2019
DOI: 10.1177/0300891619868013
|View full text |Cite
|
Sign up to set email alerts
|

Pressurized IntraPeritoneal Aerosol Chemotherapy (PIPAC) in patients with peritoneal metastasized colorectal, appendiceal and small bowel cancer

Abstract: Background: Patients with intestinal cancer (colorectal, appendiceal, and small bowel) with peritoneal metastases (PM) have a poor prognosis. We assessed whether pressurized intraperitoneal aerosol chemotherapy (PIPAC) together with systemic chemotherapy is an effective treatment option for these entities in palliative intent. Methods: Between November 2015 and February 2018, prospective data registry was performed (NCT03100708). Thirteen patients with intestinal cancer (median age 61 years [range 49–77]) unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Another aspect, with alleged relevance for the palliative management of these advanced CRC patients, was reflected by our observation that PIPAC substantially reduced ascites formation. Similar observations have been made when using PIPAC-directed therapy in PM for other diseases [20]. When we followed all our 24 patients, we recorded a median survival of 37.6 (range 10.2-47.0) months from the time of PM diagnosis, whereas it was 20.5 (range 0.13-34.7) months following the start of the first PIPAC session.…”
Section: Discussionsupporting
confidence: 79%
“…Another aspect, with alleged relevance for the palliative management of these advanced CRC patients, was reflected by our observation that PIPAC substantially reduced ascites formation. Similar observations have been made when using PIPAC-directed therapy in PM for other diseases [20]. When we followed all our 24 patients, we recorded a median survival of 37.6 (range 10.2-47.0) months from the time of PM diagnosis, whereas it was 20.5 (range 0.13-34.7) months following the start of the first PIPAC session.…”
Section: Discussionsupporting
confidence: 79%
“…A second most common indication for PIPAC is a refractory accumulation of ascites, which impairs quality of life [ 16 ]. It has been reported that PIPAC is an excellent method to control ascites, thus it improves the quality of life at the final stages of the disease [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…As described by our group (Gockel et al 2018(Gockel et al , 2020 and others (Hübner et al 2017;Nowacki et al 2018), the PIPAC procedure was performed laparoscopically and under general anesthesia, strictly following our internal standard operating procedures (SOP). First, 12 mmHg capnoperitoneum was induced via a mini-laparotomy measuring 1-2 cm.…”
Section: Surgical Proceduresmentioning
confidence: 99%